(untitled) ("Journal "U". Economy. Management. Finance.", 2025)
Central banks play an important role in managing foreign exchange reserves and stabilizing national currencies. The article discusses the mechanisms of regulation and methods of managing foreign exchange reserves, with an emphasis on the practices of the Central Bank of the Russian Federation. Based on statistical data from 2020 to 2024, the effectiveness of central banks’ actions in conditions of economic instability is analyzed. Mathematical modeling methods for predicting the impact of monetary policy on the stability of currencies are also being investigated. In conclusion, the importance of managing foreign exchange reserves for economic stability is emphasized.